Correlación genética de los caracteres productivos, reproductivos y corporales en bovinos de raza Guzerat importados a Ecuador entre 2017-2022 - Domínguez Zambrano, Kerly Milena (2024)
The objective was to estimate the genetic correlation and the productive, reproductive and body characteristics in Guzerat bulls offered by commercial semen companies in Ecuador during the period 2017 - 2022. The data were obtained from 23 bulls offered in catalogs of commercial semen houses of Guzerat breed, the transmission values were tabulated and descriptive statistics were obtained. Pearson's coefficient with a significance of 5% was used to establish the associativity of the variables and a linear regression for the trend of the parameters evaluated as a function of the year of birth of the bulls. Results showed negative correlations between PTA Milk and weights (r=-0.52 to-0.44, p<0.01 to <0.04), and positive correlations between PTA Fat and weights (r=0.67 to 0.80, p<0.0006 to <0.0001). Weaning weight is positively related to later weights and maternal weight (r=0.67 to 0.93, p<0.0004 to <0.0001). Age at first calving shows negative correlation with stability (r=-0.59, p<0.003) and positive correlation with scrotal circumference (r=0.79, p<0.0001). Body structure is positively related to PTA fat and weights (r=0.48 to 0.72, p=0.04 to <0.0003), and muscularity shows negative correlations with PTA fat and weights (r=-0.52 to -0.8, p=0.02 to <0.0001), and with age at first calving (r=-0.65, p<0.002). Scrotal perimeters were positively associated with body structure (r=0.49 to 0.65, p<0.03 to <0.0019) and negatively associated with muscularity (r=-0.52 to -0.55, p<0.02 to <0.01). Genetic trends were not significant (p>0.05) and did not show favorable annual gains.